2018
DOI: 10.1159/000490260
|View full text |Cite|
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy as an Alternative Treatment for Patients with Hepatocellular Carcinoma Compared to Sorafenib: A Propensity Score Analysis

Abstract: <b><i>Background and Aims:</i></b> Stereotactic body radiation therapy (SBRT) has emerged as a safe and effective treatment for patients with hepatocellular carcinoma (HCC), but its role in patients with advanced HCC is not yet defined. In this study, we aim to assess the efficacy and safety of SBRT in comparison to sorafenib treatment in patients with advanced HCC. <b><i>Methods:</i></b> We included 901 patients treated with sorafenib at six tertiary centers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 57 publications
1
25
0
4
Order By: Relevance
“…Recently, several prospective studies have reported an encouraging outcome of stereotactic body radiotherapy (SBRT) for selected HCC patients with response rates of 40-70% (complete and partial responses), 1-year local control rates of 75-95%, and OS rates of 55-94% [5][6][7][8][9][10]. A randomized trial on the comparison between sorafenib alone and transcatheter arterial chemoembolization (TACE) followed by fractionated radiotherapy (RT) demonstrated superior response and survival by TACE plus RT and supported the role of RT in the multimodality treatments of patients with macrovascular invasion (MVI) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several prospective studies have reported an encouraging outcome of stereotactic body radiotherapy (SBRT) for selected HCC patients with response rates of 40-70% (complete and partial responses), 1-year local control rates of 75-95%, and OS rates of 55-94% [5][6][7][8][9][10]. A randomized trial on the comparison between sorafenib alone and transcatheter arterial chemoembolization (TACE) followed by fractionated radiotherapy (RT) demonstrated superior response and survival by TACE plus RT and supported the role of RT in the multimodality treatments of patients with macrovascular invasion (MVI) [11].…”
Section: Introductionmentioning
confidence: 99%
“…The SBRT cohort consisted of 35 consecutive patients with 49 HCC lesions who have been treated in the Department of Radiation Oncology of the University Hospital Freiburg (Germany) between 2012 and 2016 and which have partly been published elsewhere [ 6 , 13 ]. Patients treated with SBRT who received prior TACE were not included in the TACE group.…”
Section: Methodsmentioning
confidence: 99%
“…In order to exactly define the radiation field, patients were immobilized in supine position with a vacuum cushion (BlueBAG BodyFIX, Innovative Technologies Völp, Innsbruck, Austria) and underwent 4 dimensional-CT (4D CT, Brilliance CT Big Bore, Philips Medical Systems, Cleveland, OH) as previously described [ 6 , 13 ]. For the 4D acquisition (Mayo Clinic Respiratory feedback system), we monitored breathing which was reduced with an abdominal compression method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In einer retrospektiv durchgeführten Propensity-Score-Analyse wurden 122 Patienten, die mittels SBRT behandelt worden sind, mit Patienten unter Sorafenib-Therapie verglichen. Die Ergebnisse deuteten auf ein verbessertes mittleres Gesamtüberleben von 17,0 Monaten (10,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)2) im Vergleich zu den mit Sorafenib behandelten Patienten von 9,6 Monaten (8,6-10,7) hin [36]. Trotz der vielversprechenden Ergebnisse sind jedoch das retrospektive Studiendesign der Studie und die limitierte Anzahl an Patienten zu beachten, sodass Ergebnisse von prospektiven Studien abzuwarten sind.…”
Section: Diskussionunclassified